Who hits harder: The Nordic skier or aerial jumper? - Wylie, D. P. (1999)
Computer modeling is used to estimate physical quantities that are difficult to measure, in this case, the landing shock experienced by ski jumpers. The landing shock is difficult to measure because attaching instruments to the skiers would affect their balance and possibly cause them to fall or reduce their performance. Using basic principals of physics, the flight trajectories of two forms of competitive ski jumping, Freestyle Aerialist and Nordic Jumpers, were modeled and the landing shocks compared. The model uses physical quantities such as the takeoff inclination, takeoff height, the shape of the hill, and the vertical drop to the landing. The landing shock is calculated from the velocity of the skier and angle which he or she hits the hill. For comparison to other sports, the landing shock is converted to a vertical drop to a flat surface. The model shows that Freestyle Aerialist have landing shocks equivalent to a vertical drop of 20 feet to a flat surface. This is over twice the landing shock of the Nordic Jumpers even though the Nordic Jumpers travel at twice the velocity and fall twice as far.